2013
DOI: 10.1051/0004-6361/201321453
|View full text |Cite
|
Sign up to set email alerts
|

CO2formation on interstellar dust grains: a detailed study of the barrier of the CO + O channel

Abstract: Context. The formation of carbon dioxide in quiescent regions of molecular clouds has not yet been fully understood, even though CO 2 is one of the most abundant species in interstellar ices. Aims. CO 2 formation is studied via oxidation of CO molecules on cold surfaces under conditions close to those encountered in quiescent molecular clouds. Methods. Carbon monoxide and oxygen atoms are codeposited using two differentially pumped beam lines on two different surfaces (amorphous water ice or oxydized graphite)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 33 publications
(37 reference statements)
1
44
0
Order By: Relevance
“…Recently, Minissale et al (2013b) have confirmed these results and estimated an activation barrier of about 600 K/k b . Recently, Noble et al (2011) and Oba et al (2011) have shown experimentally the CO 2 formation through reaction (e), but no consistent values were obtained for the activation barrier.…”
Section: Astrophysical Conclusionmentioning
confidence: 54%
See 1 more Smart Citation
“…Recently, Minissale et al (2013b) have confirmed these results and estimated an activation barrier of about 600 K/k b . Recently, Noble et al (2011) and Oba et al (2011) have shown experimentally the CO 2 formation through reaction (e), but no consistent values were obtained for the activation barrier.…”
Section: Astrophysical Conclusionmentioning
confidence: 54%
“…The model used to fit our experimental data is very similar to the one described in and Minissale et al (2013b. It is composed of five differential equations, one for each of the species considered: H 2 CO molecules, deposited on the surface; O atoms, coming exclusively from the beam; O 3 and CO 2 , formed only on the surface; and finally O 2 , coming both from the beam and formed on the surface.…”
Section: Appendix B: Rate Equationsmentioning
confidence: 99%
“…Thus such a CO2 ice-rich zone appears characteristic of the outer parts of the infall-dominated disc independent of the exact parameters used in the chemical model within the framework of the two-phase model considered here (although they do change the abundances quantatively). In fact, two additional pathways to CO2 have recently been experimentally verified, namely CO+O with EA = 1000 K and H2CO+O with EA = 335 K (Minissale et al 2013(Minissale et al , 2015. Currently, they are not included in the chemical network, but are expected to positively contribute to the CO2 production.…”
Section: Diffusion and Quantum Tunneling Barriersmentioning
confidence: 99%
“…21 Diffusing oxygen atoms have also been implicated in the formation of CO 2 through O + CO -CO 2 . [22][23][24] This pathway for the formation of molecular species from adsorbates is generally known as the Langmuir-Hinshelwood mechanism. 25 In laboratory experiments using amorphous solid water, formation of ground state 3 S À g (from OH + O( 3 P) with DH = À68 kJ mol À1 ) and excited state 1 D g O 2 (from OH + O( 3 P) with DH = 26 kJ mol À1 ) was found following electronic excitation of the ASW with 157 nm irradiation at 90 K. 17 This process for O 2 formation follows a nonequilibrium route, involves higher electronic states and differs from the processes considered in temperature-programmed desorption experiments.…”
Section: Introductionmentioning
confidence: 99%